Bio-equivalence Study of Two Oral Flumequine Formulations (Flumisol® and Maquin®) in Broiler Chickens - El-Hanbally, Saber (Journal of Medical Biomedical and Applied Sciences, 2016)
The present study was designed to assess the comparative bio-equivalence of Flumisol®and Maquin® in healthy broiler chickens after oral administration of both products in a dose of 12 mg flumequine /kg.b.wt. Twenty four broiler chickens were divided equally into two groups (12 chickens for each group). The first group was designed to study the pharmacokinetics of Flumisol®, while the 2nd group was designed to study the pharmacokinetics of Maquin®. Each broiler chicken in both groups was orally administered with 12 mg flumequine /kg b.wt. Blood samples were obtained from the wing vein and collected immediately before and at 0.08, 0.16, 0.25, 0.5, 1, 2, 4, 6, 8, 12 and 24 hours after a single oral administration. The disposition kinetics of Flumisol® and Maquin® following oral administration of 12 mg flumequine/kg b.wt, revealed that the maximum blood concentration [Cmax] were 1.88 and 1.76 g/ml, attained at [tmax] of 1.42 and 1.41 hours, respectively. In conclusion: Maquin® is bioequivalent to Flumisol® since the ratios of Cmax, AUC0􀀀24 and AUC0􀀀1 (T/R) were 0.93, 0.89 and 0.88, respectively. These are within the Bio-equivalence acceptance range. Flumisol® and Maquin® are therefore bioequivalent and interchangeable.